The Perceived Complexity of Learning Tasks Influences Students’ Collaborative Interactions in Immersive Virtual Reality - Matovu, Henry; Won, Mihye; Hernandez-Alvarado, Ricardo Bruno; Ungu, Dewi Ayu Kencana; Treagust, David; Tsai, C.C.; Mocerino, Mauro; Tasker, R. (2024)
This study investigated how different learning tasks influence students’ collaborative interactions in immersive Virtual Reality (iVR). A set of chemistry learning activities was designed with iVR, and 35 pairs of undergraduate students went through the activities. Videos of students’ interactions were analysed to identify patterns in students’ physical, conceptual, and social interactions. When students were manipulating conceptually familiar virtual objects (several water molecules), they perceived the tasks as a simple extension of prior knowledge and did not attempt to explore the 3D visualisation much. They did not move around to take different perspectives, and conceptual discussions were brief. Their prior power relations (leader–follower) carried over in iVR environments. In contrast, when conceptually unfamiliar chemical structures (protein enzyme) were displayed, students perceived the tasks as complex, demanding a new mode of learning. They spontaneously moved around to explore and appreciate the 3D visualisation of iVR. Walking to different positions to observe the virtual objects from multiple angles, students engaged in more collaborative, exploratory conceptual discussions. As the perceived complexity of learning tasks or virtual objects triggers different collaborative interactions amongst students, careful considerations need to be placed on the design of iVR tasks to encourage productive collaborative learning.